(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores effective strategies for teaching vocabulary to secondary school students, with particular emphasis on pedagogically sound classroom practices that promote long-term retention and meaningful lexical use. Drawing on theories of second language acquisition and vocabulary pedagogy, the article analyzes contextualized instruction, explicit and implicit teaching approaches, learner-centered strategies, and the integration of digital tools in vocabulary learning. The discussion highlights the importance of systematic vocabulary instruction that supports both receptive and productive lexical development.